EVALUASI IMPLEMENTASI PROGRAM SERTIFIKASI GURU DALAM JABATAN DI KOTA BEKASI - Juniati Harahap; Wahyudin Nur Nasution; Afrahul Fadhila Daulai (Sekolah Tinggi Agama Islam Al Hidayah, 2014)
This research needs to be done to determine the extent to which the program is implemented effectively so that the committee can take effective measures to improve, maintain, or improve performance. In addition, this research is necessary because since the implementation of the teacher certification program in the city of Bekasi have so far not been evaluated. The research was conducted through a recording situation occurs in the context of the issues discussed through observation, interviews, and documentation study then the results are grouped into three components, namely (1) antecedent (2) Taransactions, and (3) Outcome. Phase antecedent except in accordance with the evaluation criteria on the availability of the document cabinets, imprecision of time collecting and verifying data format validation implementation. Phase transactions are in accordance with the criteria established except on receipt of Learning Module. Phase Outcomes in accordance with the all evaluation criteria.